A Novel Approach for grid integration of Cascaded H-bridge Multilevel Inverter Under Partial Shading Condition - Swetapadma Panigrahi; Amarnath Thakur (Institute of Advanced Engineering and Science, 2018)
A modular cascaded H-bridge PV inverter system is presented in this paper. The modular structure of PV inverter helps in obtaining the maximum output power of PV system along with increase the overall efficiency of the whole system. Moreover to utilize the system up to the best a distributed MPPT controller is attached with each PV panel. As partial shading causes power imbalance at the converter output that leads to imbalance grid current, a control technique called the modulation compensation is adopted in such a way that if three phase unbalanced voltage varies directly according to unbalanced power, the injected zero sequence voltage components make the grid current balanced.